Regulation of HSC development and function by Lin28b - Cox, Grant; Kobayashi, Michihiro; Rudd, Brian D.; Yoshimoto, Momoko (Frontiers in Cell and Developmental Biology, 2025)
Hematopoietic stem cells (HSCs) provide all kinds of blood cells for life while maintaining self-renewal ability. During development, HSCs are first produced in the mouse embryo around embryonic day (E) 11. At this time, only one or two transplantable HSCs can be detected per embryo. Then, HSCs migrate to the fetal liver, where the number of HSCs rapidly increases, showing enhanced self-renewal ability. After birth, a transition occurs from the rapidly proliferating fetal HSCs to the more slowly dividing adult HSCs, which ends by 3–4 weeks of age. It is known that fetal HSCs express distinct surface markers and transcriptomes and produce a variety of distinct immune cells that are not made by adult HSCs. Accumulating evidence indicates that the ontogeny of the hematopoietic system is driven by a highly conserved and developmentally regulated RNA binding protein known as Lin28b. Lin28b is predominantly expressed in the fetal hematopoietic stem and progenitor cells (HSPCs) and regulates the developmental switch from fetal to adult HSCs. In this review, we will provide an overview of how Lin28b regulates the expansion and differentiation of HSCs in early life. These insights can be taken into consideration when developing ex vivo HSC expansion utilizing such physiological characteristics of HSCs.